A new paradigm for international disease control: lessons learned from polio eradication in Southeast Asia. - Andrus, J K (2001)
OBJECTIVES: This study evaluated the impact of international coordination on polio eradication in Southeast Asia. METHODS: Active surveillance systems for acute flaccid paralysis were assessed. Analyses focused on surveillance proficiency and polio incidence. RESULTS: Ten countries coordinated activities. Importations occurred and were rapidly contained in China and Myanmar. Countries that have been free of indigenous polio transmission for at least 3 years include Sri Lanka, Indonesia, Myanmar, and Thailand. In the remaining endemic countries--India, Nepal, and Bangladesh--poliovirus transmission has been substantially reduced; however, these countries still harbor the world's largest polio reservoir. CONCLUSIONS: Unprecedented international coordination in Southeast Asia resulted in dramatic progress in polio eradication and serves as a paradigm for control of other infectious diseases such as malaria and tuberculosis.